A comparative study of lung cancer prediction using deep learning - Mugdho, Aka Mohammad; Bhuiyan, Md. Jawad Hossain; Rafin, Tawsif Mustasin; Amit, Adib Muhammad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.